The HydG enzyme generates an Fe(CO)2(CN) synthon in assembly of the FeFe hydrogenase H-cluster. - Kuchenreuther, J; Myers, W; Suess, D; Stich, T; Pelmenschikov, V; Shiigi, SA; Cramer, S; Swartz, JR; Britt, R; George, S (American Association for the Advancement of Science, 2014)
Three iron-sulfur proteins–HydE, HydF, and HydG–play a key role in the synthesis of the [2Fe]H component of the catalytic H-cluster of FeFe hydrogenase. The radical S-adenosyl-l-methionine enzyme HydG lyses free tyrosine to produce p-cresol and the CO and CN− ligands of the [2Fe]H cluster. Here, we applied stopped-flow Fourier transform infrared and electron-nuclear double resonance spectroscopies to probe the formation of HydG-bound Fe-containing species bearing CO and CN− ligands with spectroscopic signatures that evolve on the 1- to 1000-second time scale. Through study of the 13C, 15N, and 57Fe isotopologs of these intermediates and products, we identify the final HydG-bound species as an organometallic Fe(CO)2(CN) synthon that is ultimately transferred to apohydrogenase to form the [2Fe]H component of the H-cluster.